KHALIFAH AL-MUTASHIM: KAJIAN AWAL MUNDURNYA DAULAH ABBASIYAH - Mundzirin Yusuf (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
Abbasid Dynasty is one of Islamic dynasties that had ever achieved theglory which is called the golden age, particularly in the first period of its powerthat is from Khalifah al-Manshur to al-Mamun (754-813). Nevertheless, thebackwards had initially appeared in the time of Al-Mutashim because there hademerged many small kingdoms which had authorities that could not becontrolled, even the capital of Baghdad at that time had been ruled by BaniBuwaihi and Bani Seljuk. The leadership of al-Mutashim had significantlyinfluenced the fall of Abbasid Dynasty. It is believed that such fall is caused byseveral reasons, firstly, it is noted that he had neglected the importance ofknowledge; secondly, it is also found that his leadership had always enforced theteaching of Mutazilah to his people; and lastly, he, along his rule, had alwayspreferred Turks than others so that it made many other people not settled andeven caused many riots.